Creation of an alternate reality: The organization and propaganda activities of the government of national salvation from 1941 until 1944 - Mraović Marijana T. (Balcanica, 2022)
The complexity and rise of the awareness of the importance of propaganda in the Second World War, alongside improvements in the means of mass communication, influenced the emergence of institutional propaganda actions of the wartime collaborationist regime in the territory of occupied Serbia. The paper is primarily based on archive material from the Military Archives of the Ministry of Defense of the Republic of Serbia. It also includes an analysis of the methods and models of the propaganda collaborationist administration and its representatives in the period of the Council of Commissars, as well as the “Government of National Salvation” during the entire period of occupation. It describes the formation and work of the Section for State Propaganda and its connection with the German propaganda machine, in addition to highlighting some peculiarities of the propaganda placed in the public of the occupied Serbia.